2004
DOI: 10.1007/s10162-004-4047-0
|View full text |Cite
|
Sign up to set email alerts
|

Posture, Head Stability, and Orientation Recovery During Vestibular Regeneration In Pigeons

Abstract: Compensatory behavior such as oculomotor, gaze, and postural responses that occur during movement largely depend upon a functioning vestibular system. In the present study, the initial loss and subsequent recovery of postural and head stability in pigeons undergoing vestibular regeneration were examined. Adult pigeons were trained to manipulate a straight run chamber to peck an illuminated key for fluid reward. Six behavioral measures assessing performance, posture, and head stability were quantified. These in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 65 publications
2
17
0
Order By: Relevance
“…Previously, we used identical lesion methods to examine hair cell repopulation and recovery of posture, head stability, and spatial orientation during regeneration Dickman and Lim, 2004). Several interesting parallels between our current morphological findings and vestibular-dependent behavioral recovery are worth mention.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Previously, we used identical lesion methods to examine hair cell repopulation and recovery of posture, head stability, and spatial orientation during regeneration Dickman and Lim, 2004). Several interesting parallels between our current morphological findings and vestibular-dependent behavioral recovery are worth mention.…”
Section: Discussionsupporting
confidence: 55%
“…Because only bouton afferents had regenerated at this point, these fibers must convey the required information to central circuits for the establishment of vestibulo-spinal stabilization of posture. However, some staggering and head tremor remained throughout stage 1 regeneration (Dickman and Lim, 2004). In fact, the most dramatic recoveries in both morphology and behavior were observed during stage 2 regeneration.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These reflexes, however, reappear as the hair cells regenerate [99][100][101][102]104]. More recently, Dickman and Lim trained adult pigeons to run along a long chamber and peck an illuminated key to receive a fluid reward [105]. Multiple behavioral measures for assessment of performance, posture, and head stability were quantified.…”
Section: Functional Studies Examine Complex Behaviorsmentioning
confidence: 99%
“…Thus the functional return observed was likely due to a synthesis of factors other than regeneration alone, such as residual hair cell function and nonlethal repair (Baird et al 2000;Matsui et al 2003). Recently we examined head stability, posture, and orientation recovery during regeneration in pigeons trained to negotiate a maze (Dickman and Lim 2004). We found that complete vestibular loss produced profound head instability and postural ataxia that slowly recovered according to a temporal sequence of events, including increased head stability, head-tremor reduction, return of postural stability, and finally recovery of orientation and navigational abilities (Dickman and Lim 2004).…”
Section: Introductionmentioning
confidence: 99%